2022
DOI: 10.3389/fpubh.2022.956792
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of sintilimab plus chemotherapy vs. pembrolizumab plus chemotherapy for the treatment of first-line advanced or metastatic squamous NSCLC

Abstract: Background and objectiveSintilimab has superior efficacy and safety in patients with advanced or metastatic squamous non-small cell lung cancer (NSCLC), but its cost-effectiveness in China is unclear. This study is to evaluate the cost-effectiveness of sintilimab plus chemotherapy vs. pembrolizumab plus chemotherapy for locally advanced or metastatic squamous NSCLC in China.MethodsFrom the perspective of the Chinese health system, the partitioned survival model with three health states was established in a 3-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In these settings, clinicians and decision-makers can leverage knowledge of economics to advance policy discussions about health care costs and to take action on accessibility, affordability, and value for use of these novel immunotherapies. Although there is no cost-effectiveness analysis study of sintilimab in the treatment of OSCC, some studies have reported that sintilimab plus chemotherapy is cost-effective in the first-line therapy of locally advanced or metastatic non-small cell lung cancer (31,32). Moreover, the combination of sintilimab plus bevacizumab is also likely to be a cost-effective option compared with sorafenib as the first-line treatment of patients with unresectable hepatocellular carcinoma in China (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…In these settings, clinicians and decision-makers can leverage knowledge of economics to advance policy discussions about health care costs and to take action on accessibility, affordability, and value for use of these novel immunotherapies. Although there is no cost-effectiveness analysis study of sintilimab in the treatment of OSCC, some studies have reported that sintilimab plus chemotherapy is cost-effective in the first-line therapy of locally advanced or metastatic non-small cell lung cancer (31,32). Moreover, the combination of sintilimab plus bevacizumab is also likely to be a cost-effective option compared with sorafenib as the first-line treatment of patients with unresectable hepatocellular carcinoma in China (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, another study compared the economic value of sintilimab plus chemotherapy with pembrolizumab plus chemotherapy for locally advanced or metastatic squamous NSCLC from the perspective of the Chinese health system. Owing to the price advantage, a sintilimab-based strategy was considered the optimal choice rather than the pembrolizumab-based treatment ( Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…16 44 Pembrolizumab showed good efficacy and safety for patients with advanced NSCLC; however, it was rarely used and not a cost-effective option in China due to its high price. 45 Although the cost of sintilimab was much lower than pembrolizumab, the prescriptions were also less as it was not included in clinical guidelines for lung cancer during the study period. 44 Several limitations of this study need to be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…Bevacizumab, ranked 14th in all antineoplastic drug prescriptions, was available for lung cancer treatment and added to the medical insurance list in China in 2017 16 44. Pembrolizumab showed good efficacy and safety for patients with advanced NSCLC; however, it was rarely used and not a cost-effective option in China due to its high price 45. Although the cost of sintilimab was much lower than pembrolizumab, the prescriptions were also less as it was not included in clinical guidelines for lung cancer during the study period 44…”
Section: Discussionmentioning
confidence: 99%